2021
DOI: 10.1037/gdn0000138
|View full text |Cite
|
Sign up to set email alerts
|

Group relationships during a dialectical behavior therapy skills training program for the treatment of alcohol and concurrent substance use disorders: Evidence and theoretical considerations.

Abstract: Objective: Dialectical behavior therapy Skills Training (DBT-ST) is an effective group intervention for alcohol use disorder (AUD) and concurrent substance use disorders. However, no studies have empirically investigated group relationships within DBT-ST programs. Therefore, this research aims at investigating changes in positive work relationships (PWR) and negative relationships (NR) among members, as well as between members and leaders, during a 3-month DBT-ST program for AUD and other substance use disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 71 publications
(113 reference statements)
0
2
1
Order By: Relevance
“…In contrast, previous research has shown mixed findings on the relationship between the client and peers in substance use disorder populations: some research found a significant association between group cohesion and intervention outcomes, and group processes and outcomes,32–37 while other research found no significant association between group cohesion and outcomes 38 39. Even though there seems to be no consensus in the literature on the association between the relationship between client and peers and intervention outcomes for the general adult population, we argue that there could be a strong association for older adults.…”
Section: Discussioncontrasting
confidence: 85%
“…In contrast, previous research has shown mixed findings on the relationship between the client and peers in substance use disorder populations: some research found a significant association between group cohesion and intervention outcomes, and group processes and outcomes,32–37 while other research found no significant association between group cohesion and outcomes 38 39. Even though there seems to be no consensus in the literature on the association between the relationship between client and peers and intervention outcomes for the general adult population, we argue that there could be a strong association for older adults.…”
Section: Discussioncontrasting
confidence: 85%
“…Third, while a large literature highlights the importance of the therapeutic alliance in DBT and other therapies, few have examined potentially relevant therapeutic processes within the DBT skills group. One recent study found that the strength of relationships among members with each other and with group leaders in DBT skills training was associated with individual treatment outcomes (Cavicchioli et al, 2020). Understanding the role of group processes in client treatment is particularly relevant for racially, ethnically, and culturally diverse clients, as group harmony and interdependent functioning was a key cultural value and priority for several participants in the reviewed studies (e.g., Cheng & Merrick, 2017; Yang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In SUD populations, there have been mixed findings on group cohesion. Some research has found a significant relationship between group cohesion (or group relationships more broadly), and group processes and outcomes [16][17][18][19][20][21]. Other research has found no significant association [22,23], or found it to be related to other outcome variables, such as psychological distress, however not reductions in substance use [24].…”
Section: Group Cohesionmentioning
confidence: 99%